Evaluation of the effect of ultraviolet light polymerized clear adhesive on shear and tensile bond strength of heat cure denture base resin to the cobalt-chromium retentive minor connector: An in vitro study - Minal Sanjay Kumthekar; Shivsagar Tewary; Pronob Kumar Sanyal (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of this study is to evaluate the efficacy of new material ultraviolet (UV) light polymerized clear adhesive on shear and tensile bond strength of heat cure denture base resin (Polymethylmethacrylate (PMMA)) to cobalt-chromium (Co-Cr) retentive minor connector. Setting and Design: Comparative evaluation- In-vitro study. Materials and Methods: Sixty samples of Co-Cr plates mimicking minor connectors were fabricated. Thirty samples were coated with new material UV light polymerized clear adhesive and cured under UV light source for 10 min. In gun-metal flask, metal plates were placed in the lower compartment over it. Heat cure acrylic resin was packed in the dough stage with the help of clamps and processed according to the manufacturer's instructions. Samples were kept in artificial saliva for 90 days. Shear and tensile bond strengths were calculated of each sample with a Universal testing machine, and results were statistically analyzed. Type of bond failure was observed for each sample under stereomicroscope. Statistical Analysis Used: Unpaired t test. Results: Tensile bond strength, as well as shear bond strength, showed that 0.93 N and 1.64 N respectively for without application of new adhesive was more as compared to that of samples with the application of new adhesive which is 0.75 N and 1.54 N respectively. Bond failure was found to be an adhesive failure in resin-metal interface. Conclusions: Excellent bonding seen between the new adhesive and acrylic interface but limited effect on the metal interface. To increase bond strength between metal and resin interface, some surface treatment with the metal surface is needed to increase the bonding of the new adhesive to the metal surface.